Systematically incorporating spectrum-selective radiative cooling into building performance simulation: Numerical integration method and experimental validation. (15th April 2022) - Bu, Fan; Yan, Da; Tan, Gang; Sun, Hongsan; An, Jingjing
Highlights: A built-in numerical method of radiative cooling in building simulation is raised. Detailed experimental validation of the integration method is performed. Energy saving of radiative cooling in a strip mall in six climates is analyzed. A generalized and easily-usable simulation tool with built-in LRSIM is provided. Abstract: Besides highly reflecting solar energy, the spectrum-selective radiative cooling materials (RCMs) dissipate heat to outer space especially through the atmospheric window (e.g., 8–13 μm) and achieve sub-ambient temperature under direct sunlight. Not only potentially contributing to Earth's heat rebalance, the daytime radiative cooling technology but also presents promising applications to building facades as a passive 'zero-energy' cooling method. Although there has been a large amount of radiative cooling materials developed recently due to the wavelength scale photonic material design, the wide application of radiative cooling materials to buildings faces challenges, including the barriers of scalable manufacturing and the lack of industry acceptable simulation tools for designers and engineers. Deliberating the major impacting factors such as moisture variation in atmosphere, this study designed a systematic strategy of incorporating spectrum-selective radiative cooling with whole-building performance simulation by developing a new long-wavelength radiation spectrum integral module (LRSIM) suitable for being built into the state-space model, like the DeST tool. Reduced-scale controllable experiments have validated the accuracy of LRSIM, giving < 3% deviation for the spectrum-based long-wavelength radiation calculation. Subsequently, experimental results from full-scale model houses were utilized to further validate the DeST tool embedded with LRSIM for building application of spectrum-selective radiative cooling materials. Indoor air temperature deviation < 1 °C was observed between the simulated and measured data, indicating the compelling prediction power of the integrated tool for radiative cooling modeling. Simulation analysis to a single-story commercial building at six locations around the world has shown energy-saving potential of 14–42% for an example radiative cooling material. Different from other customized plug-in integration, the experimentally validated DeST with built-in LRSIM will provide architecture designers and application engineers a general-purpose and easily-usable tool for promoting adoption of radiative cooling technology in buildings.